Interannual Variability in the Source Location of North African Dust Transported to the Amazon - (:unkn) unknown (My University, 2022)
African dust is transported to South America (SA) every winter and spring. Hypotheses suggest that either Western or Central North Africa (e.g., Bodélé Depression) is the main source of transported dust, yet these notions remain largely untested with geochemical data. Using 2 years of isotopic measurements (strontium and neodymium) of African dust collected in SA integrated into a statistical model, we identified strong interannual variability in dust source region. Central North Africa supplied 44% of long-range transported dust in winter 2016 while the Western region accounted for 53% of dust in winter 2014. We propose the variability is due to differences in the strength of the Libyan High and precipitation over the Gulf of Guinea and Atlantic Ocean between the 2 years. Our findings can improve constraints of dust nutrient deposition and predictions of how changes in climate impact the source and magnitude of dust transported to the Amazon.
Keywords: African Research